1985
DOI: 10.1007/bf00225418
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical investigation of urotensins in the caudal spinal cord of four species of elasmobranchs and the lamprey, Lampetra japonica

Abstract: In the four species of elasmobranchs examined (Triakis scyllia, Heterodontus japonicus, Scyliorhinus torazame, Dasyatis akajei), all identifiable caudal neurosecretory cells and their corresponding neurohemal areas showed urotensin II (UII)-immunoreactivity with varied intensity. To localize urotensin I (UI) in the caudal neurosecretory system of the dogfish, Triakis scyllia, h-CRF (1-20) antiserum that cross-reacts with UI was used in place of UI antiserum. CRF/UI-immunoreactivity was demonstrated in the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
2

Year Published

1986
1986
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 13 publications
2
7
0
2
Order By: Relevance
“…The axons of neurons of both types terminated in the neurohemal areas. These results were similar to those demonstrated by CRF and Ull antisera in the dog fish, Triakis scyllia (OWADA et al, 1985b). FISHER et al (1984) observed that all the caudal neurosecretory neurons in the white sucker reacted with UI antiserum, and considered the hypothesis for the existence of two types of neurons containing UI and UII, respectively, to be untenable.…”
Section: Methodssupporting
confidence: 80%
See 4 more Smart Citations
“…The axons of neurons of both types terminated in the neurohemal areas. These results were similar to those demonstrated by CRF and Ull antisera in the dog fish, Triakis scyllia (OWADA et al, 1985b). FISHER et al (1984) observed that all the caudal neurosecretory neurons in the white sucker reacted with UI antiserum, and considered the hypothesis for the existence of two types of neurons containing UI and UII, respectively, to be untenable.…”
Section: Methodssupporting
confidence: 80%
“…The UI-immunoreactive neurons were first demonstrated in elasmobranchs in the present study, although a CRF/UI-like substance has already been demonstrated using CRF antiserum (.OwADA et al, 1985b). At least two types of neurons were identified: those immunoreactive with both UI and Ull antisera ( Fig.…”
Section: Methodssupporting
confidence: 48%
See 3 more Smart Citations